To report, or not to report? From code of silence suppositions within sport to public secrecy realities - Moriconi, M.; Cima, C. (Crime, Law and Social Change, 2020)
One of the main obstacles to detect undesirable conducts such as manipulation of games and competitions, and to combat corrupt behaviour in the sports world is the existence of the so-called “code of silence” among the sport’s actors. Therefore, integrity educational campaigns, codes of conduct, ethics and disciplinary norms include the obligation to report any suspicion, approach, tentative or case of match-fixing. In some countries, such as Portugal, the obligation to denounce is incorporated into criminal law. Although several protected reporting channels have been implemented for sport institutions and federations to encourage whistle-blowing practices, the level of denouncement is still low. Through the analysis of official discourses, ethnography and interviews with key informants, this article demonstrates that despite the formal norms, reporting on corruption in sport, mainly match-fixing, is a dangerous practice that can have serious consequences for the athletes’ career. More than a code of silence within sports, what exist is a series of public secrecies that deliberately recognize the existence of informal institutions that create and materialize those dangers. However, while integrity actors show awareness of the situation, the official narrative and formal norms avoid considering these problems and, moreover, throw this evidence out of the integrity narrative framework. The result is a delegitimate and non-realistic narrative that pushes sports actors to keep quiet more than promoting ethical behaviours and whistle-blowing.